Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1461444819840021
|View full text |Cite
|
Sign up to set email alerts
|

Instagram: Friend or foe? The application’s association with psychological well-being

Abstract: The current study examined the association between the social media application Instagram and its users’ psychological well-being. Participants, both Instagram users and non-users, were surveyed online on measures of depression, anxiety, loneliness, self-esteem, body image, and social comparison. Participants who reported having an Instagram account were also asked about their time spent on Instagram and Instagram anxiety. To understand the association between Instagram and psychological well-being, the study’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 44 publications
4
49
1
2
Order By: Relevance
“…These SNSs have different properties which may influence how they are related to loneliness, with Instagram used to follow people not known offline as well as friends, and WhatsApp used to create more private groups (Pittman & Reich, 2016). Future research could examine how the network properties of these different types of SNSs are associated with loneliness (Mackson et al, 2019;Yang, 2016) and adjustment to University (Yang & Lee, 2020). More broadly, our study is limited by the sample it used (Henrich et al, 2010;Pollet & Saxton, 2019;Simons et al, 2017), and the degree to which our findings would generalize beyond student samples in a Western context is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These SNSs have different properties which may influence how they are related to loneliness, with Instagram used to follow people not known offline as well as friends, and WhatsApp used to create more private groups (Pittman & Reich, 2016). Future research could examine how the network properties of these different types of SNSs are associated with loneliness (Mackson et al, 2019;Yang, 2016) and adjustment to University (Yang & Lee, 2020). More broadly, our study is limited by the sample it used (Henrich et al, 2010;Pollet & Saxton, 2019;Simons et al, 2017), and the degree to which our findings would generalize beyond student samples in a Western context is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, peer groups influence adolescents' behavior (Global Kids Online 2019;Haddon 2013). In regard to negative influences, SNS pose risks to adolescents' wellbeing, i. e., the Fear of Missing Out (FoMO, see Przybylski et al 2013) and so does the peer group (Mackson, Brochu, and Schneider 2019). These arguments in mind, we argue that pressure in the context of SNS might originate from the peers as adolescents might perceive pressure to align their needs with peer expectations.…”
Section: Introductionmentioning
confidence: 92%
“…11-to 16-year-olds responded with «cyber bullying,» «seeing stuff you don't want to see, like porn,» «making you feel envious of others,» «strangers,» and «it puts you under pressure to make your life out to be amazing» (Lilley, Ball, and Vernon 2014, 11) when asked about the downsides of SNS. What becomes obvious is the risk of experiencing «upsetting and potentially harmful content and practices» (Swist et al 2015, 68) which have been shown to be associated with decreased self-efficacy, happiness, and satisfaction with life, and increased depression and loneliness (Mackson, Brochu, and Schneider 2019;Santarossa and Woodruff 2017).…”
Section: Adolescents' Use Of Instagrammentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that following other parents and their domestic self-presentations online makes Raisa feel vulnerable. Scholars have suggested that social media triggers social comparison that causes users to relate other people's perceived achievements to those of their own, and to believe that others have it better (Lee, 2014;Mackson et al, 2019Mackson et al, : 2164Vannucci et al, 2017). The social context of mothering can amplify such networked sensibility.…”
Section: Experiencesmentioning
confidence: 99%